Captura incidental de um tubarão-baleia, Rhincodon typus (Orectolobiformes, Rhincodontidae), na costa do Ceará, Nordeste do Brasil - Faria, Vicente V.; Venancio, Iury M.; Basilio, Thiago H.; Silveira, Leonardo M.; Jucá-Queiroz, Bruno; Gadig, Otto B.F. [UNESP]; Furtadoneto, Manuel A.A. (My University, 2009)
A whale shark, Rhincodon typus, was incidentally captured off Ceará on January 2009, during gillnet fishery. This is the second occurrence record for this species off the State and the first including material deposited in a scientific collection.
Incidental capture of a whale shark, Rhincodon typus (Orectolobiformes, Rhincodontidae), off Ceará, Northeastern Brazil
Keywords: Elasmobranch; Endangered species; Incidental capture; Occurrence record.; Cetacea; Chondrichthyes; Orectolobiformes; Rhincodon typus; Rhincodontidae